Biological control strategies of purple witchweed, Striga hermonthica: a review - Osman, Nadia Yasseen; Hamdani, Muhammad Saiful; Oslan, Siti Nurbaya; Mohamed Zulperi, Dzarifah; Saidi, Noor Baity (Universiti Putra Malaysia Press, 2023)
The genus of Striga spp., particularly Striga hermonthica, is an obligate root-hemiparasitic weed. Striga affects 25 African countries annually and is considered a major biotic threat to food security. This obnoxious weed species has been managed using various control strategies. However, the strategies have not been highly effective due to the complexity of the Striga life cycle and special interactions with its host. Biological control, considered a safer and ‘greener’ alternative, has drawn attention due to numerous reports on the potential of biological agents, including insects and microorganisms, to control Striga. Although researchers agree on the importance of the biocontrol approach as one of the alternative eco-friendly methods to manage Striga spp., the decreasing effectiveness of some biocontrol agents when introduced into new environments, in addition to requirements before and during the application, restricts the application of biological control on a large scale until today. This review focuses on the current knowledge of control strategies to manage Striga, emphasizing the biological control method. The challenges that limit the application of biological control to manage Striga on a broader scale are also highlighted.